2017
DOI: 10.1021/acsinfecdis.7b00017
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo-Selected Pyrazinoic Acid-Resistant Mycobacterium tuberculosis Strains Harbor Missense Mutations in the Aspartate Decarboxylase PanD and the Unfoldase ClpC1

Abstract: Through mutant selection on agar containing pyrazinoic acid (POA), the bioactive form of the prodrug pyrazinamide (PZA), we recently showed that missense mutations in the aspartate decarboxylase PanD and the unfoldase ClpC1, and loss-of-function mutation of polyketide synthases Mas and PpsA-E involved in phthiocerol dimycocerosate synthesis, cause resistance to POA and PZA in Mycobacterium tuberculosis. Here we first asked whether these in vitro-selected POA/PZA-resistant mutants are attenuated in vivo, to pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…In addition, these independent studies showed that mutations of H21 within the N-terminal region of the aspartate decarboxylase domain are also associated with POA resistance. 20,22,24,30 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, these independent studies showed that mutations of H21 within the N-terminal region of the aspartate decarboxylase domain are also associated with POA resistance. 20,22,24,30 …”
Section: Resultsmentioning
confidence: 99%
“…Sequencing of POA-resistant M. tuberculosis strains isolated from lungs of mice treated with POA revealed that missense mutations in panD constitute the predominant mechanism of resistance to POA in vivo . 24 Probing of the panD -related resistance mechanism in vitro revealed that treatment of M. bovis BCG with POA results in a depletion of intracellular coenzyme A levels. 20,25 Our observation that resistance mutations in panD prevent POA-mediated depletion of intracellular coenzyme A levels 20 and that this PanD-mediated resistance phenotype can be mimicked by supplementation of downstream metabolites of PanD such as β -alanine and pantothenate 20,22,26 suggests a role of POA in disrupting the coenzyme A biosynthetic pathway.…”
mentioning
confidence: 99%
“…Recently, numerous studies have shown that a component of the coenzyme A (CoA) biosynthetic pathway may be a molecular target of POA ( Fig. 1 ) [40][41][42][43][44][45] . Analysis of spontaneous PZA and POA resistant isolates with functional PncA revealed missense mutations in panD that encodes l -aspartate-α-decarboxylase, a rate-limiting step in the CoA biosynthetic pathway [42,44] .…”
Section: Proposed Molecular Targets For Pzamentioning
confidence: 99%
“…The C-terminal extension appears to be a hot spot for POA resistance mutations [45] . In addition to isolation of panD mutant strains in vitro, Gopal et al recovered POA resistant panD mutant strains (82% of POA resistant strains) from the lungs of mice that were infected with M. tuberculosis and treated with POA [41] . Mice infected with a panD missense mutant strain had bacterial lung burdens comparable to those infected with wild-type M. tuberculosis [41] , indicating that panD mutant strains maintain fitness in vivo.…”
Section: Proposed Molecular Targets For Pzamentioning
confidence: 99%
“…What is certain is that PZA is a prodrug that is converted into pyrazinoic acid (POA) by the enzyme pyrazinamidase, PncA (Rv2043c) 8 , and that most of the PZA clinical resistance arises from loss of function mutations in pncA. However, multiple mechanisms of action and targets have been reported for PZA [9][10][11][12][13][14][15][16][17][18] . Recently, Zhang et al reported several PZA resistant mutations that mapped to the Mtb panD gene 19,20 , suggesting it was a target of PZA.…”
mentioning
confidence: 99%